1999
DOI: 10.1037/0021-9010.84.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Can self-reported encoding strategy and recognition skill be diagnostic of performance in eyewitness identifications?

Abstract: The relationship between 3 witness factors and identification accuracy, as well as calibration and diagnosticity of confidence, was investigated. A total of 384 participants in an eyewitness experiment rated their facial recognition skill, general memory skill, and self-reported encoding strategy on a questionnaire presented after the photo-confrontation. Participants who rated themselves to be good face recognizers showed a slightly higher overall accuracy with a more diagnostic confidence-accuracy relation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(85 citation statements)
references
References 12 publications
11
72
2
Order By: Relevance
“…Behavioral research has also shown that conditions at the time of encoding influence the confidence-accuracy relationship, and our study provides evidence that it has a neural basis. As mentioned previously, in a videotaped simulated crime, Olsson and Juslin (1999) found that subjects who rated their encoding of the perpetrator as ''holistic'' (deep) rather than ''analytic'' (shallow) showed higher identification accuracy and a stronger correlation between confidence and accuracy. Frost and Weaver (1997), also using a simulated eyewitness event, showed that increasing the time of encoding could eliminate misinformation effects that led to increased misidentifications.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Behavioral research has also shown that conditions at the time of encoding influence the confidence-accuracy relationship, and our study provides evidence that it has a neural basis. As mentioned previously, in a videotaped simulated crime, Olsson and Juslin (1999) found that subjects who rated their encoding of the perpetrator as ''holistic'' (deep) rather than ''analytic'' (shallow) showed higher identification accuracy and a stronger correlation between confidence and accuracy. Frost and Weaver (1997), also using a simulated eyewitness event, showed that increasing the time of encoding could eliminate misinformation effects that led to increased misidentifications.…”
Section: Discussionmentioning
confidence: 83%
“…Olsson and Juslin (1999) found that subjects who rated their encoding of a perpetrator as ''holistic'' (deep) rather than ''analytic'' (shallow) showed higher identification accuracy and a stronger correlation between confidence and accuracy. Frost and Weaver (1997 ) showed that memory distortions from misleading information could be eliminated with a longer encoding condition and more retrieval cues.…”
Section: Introductionmentioning
confidence: 98%
“…We believe that both methods and their reasoning have their legitimization. Researchers must be cautious when deciding for one or the other method and we believe it most appropriate to report more than one measure (for methods of establishing innocent suspect choices other than the ones used here, see Clare & Lewandowsky, 2004;Fleet et al, 1987;Olsson & Juslin, 1999;Sporer, 1993Sporer, , 2007. Accuracy rates in the four different lineup types were not associated with each other.…”
Section: Discussionmentioning
confidence: 91%
“…Kneller, Memon, & Stevenage, 2001;Sporer, 1992Sporer, , 1993Sporer, , 2007, second, selected by experienced policemen who create the photo-spreads (e.g. Brigham et al, 1986;Fleet, Brigham, & Bothwell, 1987;Olsson & Juslin, 1999), or, third, the foil chosen most often (Pryke et al, 2004). Fourth, one of several foils who are rated as similar to the target is randomly selected (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of face-recognition studies have highlighted the advantage of a semantic or holistic decision-making process, as compared to a feature-based one (e.g., Olsson & Juslin, 1999). One reason for this is that trait judgements are deeper and therefore more elaborate, leading to better memory performance (e.g., Coin & Tiberghien, 1997;Gallo, Meadow, Johnson & Foster, 2008).…”
Section: And In 2005 Jeanmentioning
confidence: 99%